2010
DOI: 10.1002/eji.201040531
|View full text |Cite
|
Sign up to set email alerts
|

Increased CD127 expression on activated FOXP3+CD4+ regulatory T cells

Abstract: Regulatory T cells (Treg) are commonly identified by CD25 (IL-2Ra) surface expression and/or intracellular expression of the FOXP3 transcription factor. In addition, Treg are also characterized by low CD127 (IL-7Ra) expression when compared to conventional T cells and their biology in the periphery is considered essentially independent of IL-7. We further investigated CD127 expression on Treg and we demonstrated differential CD127 expression depending on Treg subsets considered. Notably, we observed high CD127… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
85
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 53 publications
9
85
0
2
Order By: Relevance
“…One possible explanation for the discrepancies in human studies could be that FOXP3 expression is variable in human Tregs. This suggests that additional Treg markers, such as the low expression of CD127 in these cells, may need to be added to their analysis [57,58] to give a true reflection of the levels of this important T cell subpopulation in human WAT.…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…One possible explanation for the discrepancies in human studies could be that FOXP3 expression is variable in human Tregs. This suggests that additional Treg markers, such as the low expression of CD127 in these cells, may need to be added to their analysis [57,58] to give a true reflection of the levels of this important T cell subpopulation in human WAT.…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…absence of its expression) is not an ideal biomarker for the identification of Tregs, because a fraction of early-activated Teff cells are also CD25 + FOXP3 + C-D127 low/− and thus are indistinguishable from Tregs [11]. Conversely, it has been shown in mice that CD127 is also highly expressed on Tregs upon in vitro and in vivo activation and on fraction of Tregs located in tissues [12].…”
Section: Regulatory T Cell Subsetsmentioning
confidence: 99%
“…More recently, a search for cell surface surrogates of FOXP3 (FOXP3 cannot be used to isolate viable Treg as it requires intracellular staining) has revealed that reduced expression of the IL7 receptor (CD127) is also a hallmark of the human Treg phenotype 7, 8. It has been reported that CD127 is not selective for mouse Treg, as activated murine Treg express CD127 strongly 9. The differential expression of cytokine receptors on Treg may be important in restricting survival or function as, for example, mature human Treg are dependent on exogenous IL2, but not on IL7.…”
Section: Introduction: the Treg Phenotypementioning
confidence: 99%